State of knowledge of the relationship between celiac disease and oral pathology: A scoping review. - Martin‐Masot, Rafael; Ramos-García, Pablo; Torcuato-Rubio, Encarnación; Pérez-Gaspar, María Isabel; Navas-López, Víctor Manuel; González-Moles, Miguel A.; Nestares, Teresa (Medicina Oral S.L., 2025)
Background: Celiac disease (CD) is a systemic disorder characterized by an enteropathy of highly variable clinical expression, in which the relationship with oral pathology has not yet been fully elucidated. We aimed to update the current knowledge on oral manifestations in CD, to identify evidence gaps and to point out future research lines. Material and methods: PRISMA-ScR guidelines were followed. MEDLINE/PubMed, Embase, Web of Science and Scopus were searched for primary-level observational studies to analyze the prevalence of oral pathology in CD patients, without language or publication date restrictions. Results: We included 107 studies, encompassing a total of 26148 celiac patients and 36063 controls. Our results point to several oral pathologies with higher prevalence in CD patients than in healthy controls, most notably recurrent aphthous stomatitis (RAS)(n=69 studies/12606 celiac patients), developmental enamel defects (n=61 studies/5037 patients), dental caries (n=33 studies/2730 patients), delayed eruption (n=12 studies/1062 patients), atrophic glossitis (n=10 studies/1062 patients), angular cheilitis (n=7 studies/10606 patients), gingivo-periodontal diseases (n=7 studies/1122 patients), and Sjögren's syndrome (n=5 studies/953 patients). Conclusions: CD is frequently associated with oral pathologies, including RAS, dental caries, gingivitis, decreased salivary flow, dental enamel defects and some relevant autoimmune processes, such as oral lichen planus and probably Sjögren's syndrome.
https://www.medicinaoral.com/ "This is an open access journal without any cost for the authors"
Keywords: Enfermedad celíaca; Estomatitis; Oral pathology; Celiac disease; Dental caries; Recurrent aphthous stomatitis